Assessment of Patients’ Satisfaction toward Nursing Care at Hemodialysis units - Shnishil, ali; Mansour, Khalida (Iraqi National Journal of Nursing Specialties, 2013)
Objectives: To assess patients’ satisfaction to nursing care at hemodialysis units and determine the relationship between patients’ satisfaction and patients’ demographic data. Methodology: A descriptive study was carried out at hemodialysis units of Baghdad teaching hospitals from Feb. 4 th , 2010 through Sep. 5 th, 2010. A purposive (non-probability) sample of (150) patients ta hemodialysis units ni Baghdad teaching hospitals was selected. The data were collected through the use of constructing questionnaire and by means of an interview technique with the patients; the questionnaire consists of two parts (1) demographic data (2) patients’ satisfaction to nursing care. The validity of the study questionnaire was determined through the panel of experts and the reliability of the study questionnaire was determined through the pilot study. Descriptive statistical analysis procedure (frequency, percentage and mean of score) and inferential analysis procedure (person correlation coefficient, chi-square test and t-test) were used for data analysis. Results: The findings of the study indicated that there is high satisfaction to clinical nursing care, communication /patient –nurse relationship and moderate satisfaction toward nursing health education. Not statistical significant difference between (gender, age, educational status, marital status, occupational status, frequency of hemodialysis and duration of hemodialysis). While there is a statistical significant difference between patients’ occupational status and their satisfaction toward communication /patient –nurse relationship. Recommendations: Great emphasize should be directed toward the educational aspects of hemodialysis unit by providing educational posters, guidelines, pamphlets and manuals.